Predicted Transmissibility of an Experimental Approach for a Laminated Rubber-Metal Spring - Putra, Azma; Salim, Mohd Azli; ABDULLAH, Mohd Azman (AENSI, 2014)
This paper presents a study of predicted transmissibility of an experimental approach for a laminated rubber-metal spring. Lumped parameter system approach is used to derive the mathematical model and test rig is designed to validate the analytical results. It is found that increasing the number of metal plates inside natural rubber rod, more internal resonances appear which degrades the isolation performance. However, the system shows better transmissibility at high frequency where the slope rolls off steeper that from the rubber system without the embedded metal plates